(untitled) (JURNAL KEPERAWATAN, 2018)
Abstract: Hospitalization in children is a stressful experience for both the children themselves and their parents. The number of stressors experienced by children when undergoing hospitalization interfere adversely affecting the child’s development. The hospital environment canbe a cause of stress and anxiety in children.In line with the increase in the number of children who were hospitalized late population at risk of an increase in children who have developmental disorders. The Purpose of this study was to is to analyze correlation between nurse behavior and stres of hospitalzation to Children at Pre School at Pancaran Kasih Christian Evangelical Church In Minahasa Hospital Manado. Methode in this study used descriptive analytic with cross sectional design. Sampling technique using tipe judgement sampling involved 47 respondents. Results of this study based on chi-square the views of the fisherâ€™s exact test obtained Ï value=0,012. This means that the value of Ï is less than the value of Î± (Î±=0.05), thus it can be said that H0 is rejected. Conclusion There is significant correlation between nurse behavior and stres of hospitalzation to Children at Pre School at Pancaran Kasih Christian Evangelical Church In Minahasa Hospital Manado. Keywords : Between Nurse Behavior, Stres Of Hospitalzation, Children at Pre School Abstrak: Hospitalisasi pada anak merupakan pengalaman yang penuh dengan stress, bagi anak itu sendiri maupun orang tua. Banyaknya stressor yang dialami anak ketika menjalani hospitalisasi menimbulkan dampak negatif yang menganggu perkembangan anak. Sejalan dengan peningkatan jumlah anak yang dirawat dirumah sakit akhir-akhir ini, beresiko terjadi peningkatan populasi anak yang mengalami gangguan perkembangan. Tujuan penelitian ini adalah untuk menganalisis hubungan sikap perawat dengan stress akibat hospitalisasi pada anak usia pra sekolah di RSU Pancaran Kasih GMIM Manado. Metode penelitian yang digunakan yaitu deskriptif analitik dengan rancangan cross sectional. Teknik Pengambilan Sampel pada penelitian ini yaitu tipe judgement sampling dengan jumlah 47 sampel. Hasil Penelitian berdasarkan uji chi-square yang dilihat dari fisherâ€™s exact test diperoleh nilai Ï value=0,012. Hal ini berarti nilai Ï lebih kecil dari nilai Î± (Î±=0,05), dengan demikian dapat dikatakan bahwa H0 ditolak. Kesimpulan terdapat hubungan yang signifikan antara hubungan sikap perawat dengan stress akibat hospitalisasi pada anak usia pra sekolah di RSU Pancaran Kasih GMIM Manado. Kata Kunci : Sikap Perawat, Stres Akibat Hospitalisasi, Anak Usia Pra Sekolah